Optimizing variant calling performance for hotspot cases based on ion torrent sequencing technology - Basma Nasser Abdelsalam Abdelfattah; Ayman Mohamed Eldeib; Mohamed Moustafa Ibrahim Abouelhoda (Cairo : Basma Nasser Abdelsalam Abdelfattah, 2018)
In last few years, Next generation sequencing (NGS) revolutionized in DNA sequencing research. The latest major technologies released are Illumina and Ion torrent. In this study, we analyze the performance of calling variants using both platforms. In order to compare between both platforms, we used two sequenced data sets from ion community, which contain flow spaces required by Ion torrent. We are concerned with the execution time of both platforms. Ion torrent detects genome variants faster than Illumina but with low accuracy. Moreover, we found that Ion Torrent called slightly more variants but with higher false positive rate. The hotspot option provided by ion torrent variant caller provides more accurate variant calling positions as the filtration restricted to specific positions in the genome, but this leads to time consumption. Here, we enhanced the execution time to attain the accurate positive variants using torrent variant caller by using the NOCALL variants as hotspot regions to torrent variant caller (TVC). We developed two dependent packages the first one to create the new hotspot file (mHotspot) required by TVC and the second one to rerun the TVC with mHotspot file generated to get the exact positions of variants
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Systems and Biomedical Engineering
Issued also as CD
Keywords: Ion torrent; Next generation; Variant calling